Amplifikasi Pasang Surut dan Dampaknya terhadap Perairan Pesisir Probolinggo - Edi Kusmanto; Muhammad Hasanudin; Wahyu Budi Setyawan, (OLDI (Oseanologi dan Limnologi di Indonesia), 2026)
Tidal Amplification and Its Impact to Probolinggo Coastal Waters. Rob flood that frequently struck the coast of Probolinggo is an interesting phenomenon. Tidal flood, tidal flats, and sedimentation is strongly associated with the tides. Therefore, this study of tidal amplification and its estimated impacts on the coastal waters of Probolinggo was conducted. Tidal measurements were done with RBR TWR-2050 every 5 minutes for 30 days. Measurements of flow and depth were performed with the Acoustic Doppler Current Profiler (ADCP) 1200 KHz along the trajectory of the boat. Measurements of turbidity with turbiditymeter mounted on a CTD SBE 19 Plus at 19 stations. The results showed that tidal range reached 3.00 m, much higher than in Java Sea. As a comparison, the tidal range of Tanjung Perak port in Surabaya was 1.76 m. Based on the value of Formzahl (0.85) and analysis of power spectra, Probolinggo waters were classified as mixed tide prevailing semidiurnal. There was indication of tidal amplification due to resonance of natural period of Madura Strait for 12.46 hours on M2 tidal constituent with a period of 12.42 hours that caused the tidal amplitude of Probolinggo waters reached 3 m. Impact of such amplification included the current direction which always leads to the coast, both at high and low tides that resulted in relatively high distribution of suspended sediment along the coast and around the port area. Intensive sedimentation caused the flatness and vast formation of tidal flats, up to 3 km from the coastline. Moreover, the phenomenon of tidal amplification impacted on the tidal inundation in the lower mainland when the tidal amplification occured simultaneously with the intense rain which caused the tidal flood in the coastal villages of Probolinggo.